Effect of adding bone marrow aspirate injection to core decompression on clinical outcomes in the treatment of femoral head avascular necrosis (Annals of Medical Research, 2026)
Aim: Avascular necrosis of the femoral head (ANFH) is a progressive condition that often affects young individuals and may ultimately require total hip arthroplasty (THA). Core decompression (CD) is a widely used joint-preserving surgical technique, and bone marrow aspirate concentrate (BMAC) injection has been proposed as an adjunct to enhance outcomes by promoting vascularization and cartilage repair.To compare the clinical and radiological outcomes of patients treated with CD alone versus CD combined with BMAC injection for ANFH.Materials and Methods: Patients diagnosed with ANFH who underwent CD with or without BMAC injection were retrospectively analyzed. Demographic characteristics, preoperative and 1-year Harris Hip Score (HHS), Visual Analog Scale (VAS) score, Steinberg stage, and the need for THA during follow-up were recorded. All diagnoses were confirmed by MRI and radiography.Results: A total of 42 hips (30 males, 12 females; mean age 41.8 years, range 14–66) were analyzed. BMAC injection was performed in 28 hips (66.7%) and not performed in 14 hips (33.3%). At 1-year follow-up, Steinberg stage progression was observed in 73.8% of hips, while 26.2% showed regression. THA was required in 14.3% of patients overall—7% in the BMAC group versus 28% in the CD-only group (p = 0.1). VAS scores decreased in 32% of BMAC-treated hips versus 21% in CD-only hips (p>0.05). Improvement in HHS was seen in 60% of the BMAC group versus 50% of the CD-only group (p>0.05).Conclusion: Although statistical significance was not reached, the addition of BMAC to core decompression showed a trend toward reduced THA conversion and improved hip function. These findings suggest a potential benefit that warrants further investigation in larger, prospective studies before routine use can be recommended.
Keywords: Avascular necrosis; Femoral head; Core decompression; Bone marrow aspirate concentrate; Total hip arthroplasty; Hip preservation